IMPLEMENTATION OF THE NEW INDUSTRIALIZATION STRATEGY IN THE ECONOMY - V. A. Tsvetkov; I. M. Stepnov; Yu. A. Kovalchuk (Финансы: теория и практика)
The purpose of the study was to examine further the role of the state in industrial modernization processes in the context of the new industrialization of the country’s economy, which means not only a fundamental technological renovation of the industry but also significant changes in the institutional environment. The study used the results of the comparative analysis of economic policy priorities, specific to different systems of the market economy, which made it possible to identify a number of approaches to keeping the balance between the market and state management. A method of historical and economic dynamics was used to evaluate possibilities of combining project solutions and institutional tools in the framework of national economic development objectives. The functions and efficiency of development institutions and national technology platforms are analyzed. The problems of the industrial policy and clustering of the economy as both a tool to support the industrial modernization and a set of government regulation measures are considered. The results obtained substantiate the nature and principles of the balancing tool for support of the new industrialization in Russia (national project office) that should take into account the principles of interaction along with state policy task sharing in the field of the project approach, development institutions and economic entities.